MODELISATION ET SIMULATION PAR ELEMENTS FINIES D’UN CABLE ELECTRIQUE DE PUISSANCE A 4 CONDUCTEURS - Lakrim, Abderrazak; Tahri, Driss (European Scientific Journal, ESJ, 2015)
The Electromagnetic Compatibility (EMC) has became a major constraint in the design of power electronics systems, specifically on the static converters and their connection with electricity network and with the load (Motor). Connecting cables with the electricity network, and with the load are the main transmitters of very stringent electromagnetic interference (EMI) generated by the semiconductors used (converter) operating at higher frequencies, we are particularly interested in common mode conducted interferences (CM) that are the most penalizing mode in this kind of system.